Education and the environment: a proposal for the mobile commerce of Park Barigüi (Revista LIDER, 2020)
The article aims to identify the socioenvironmental perception of street vendors to subsidize an educational program in the context of Parque Barigüi. Barigüi Park is an scenario of biodiversity and inclusion of heterogeneity in human relations, and a reference to social and ecological environment in the urban city of Curitiba-PR. This is a qualitative and quantitative research that uses the case study, semi-structured interviews and questionnaires to selected vendors. We conclude that the perception of social and environmental subjects, the lack of policy on Environmental Education for street vendors tend to become an obstacle for them, since they could act as agents of environmental education for visitors to Barigüi Park.